Introduction Artificial Neuron Networks - E. Uljaev; M. Sapayev; Sh. N. Narzullayev; E. F. Xudoyberdiyev; F. B. Sodiqova (International Journal on Integrated Education, 2022)
Nowadays, a wide range of new possibilities for the construction of intelligent systems for the control of technological processes are developing through the use of artificial neural networks. The article describes the widespread use of symbols through artificial neural networks in issues such as recognition, prediction and diagnosis, optimization, signal processing under the influence of noise, and discusses the main parameters of the artificial neural network by the authors.